Grade six students’ and teachers’ attitudes towards socio-constructivism in science education - Potgieter, Annelize; Potgieter, Marthienus Johannes (Technium Social Sciences Journal, 2021)
The aim of this study was to investigate the attitudes of Grade 6 students and their science teachers towards a socio-constructivist way of learning and teaching science, compared to the usual way of learning and teaching science; as well as the science teaching practices. The data was collected during a period of eight weeks in two rural primary schools in the Limpopo Province, South Africa. A five-week intervention was conducted during which the researchers taught science in a socio-constructivist way. Observations were conducted as well as interviews with the teachers and 10 students (5 in each school) using the CLES observation guide, CLES interview guide, CLES Actual questionnaire and CLES Preferred questionnaire. The interviewed students also participated in a focus group. The results showed that some elements of socio-constructivism were appreciated by the students and teachers and other elements not. The students’ attitudes were positive about scientific uncertainty and student negotiation and rather negative about critical voice and shared control. The attitudes of the teachers were more ambiguous.